Lopeg (Teacher Pedagogic Observation Sheet) : Development Of Instruments To Analyze The Feasibility Of Ukg Results In Sdn Percobaan Medan City - Rosmini, Paujia (JURNAL BUNGA RAMPAI USIA EMAS, 2017)
Ketua Umum PB PGRI Dr. Sulistiyo said "in 2012 in Semarang there are teachers who are liked by  the students and also the community, but when the competency test is very low value and impact on the public's trust in the teacher." This becomes one of the proof of the reality of the problematics of the effectiveness of the current UKG. UKG for teachers in the regions is coercion. As it is known that the expected value of UKG is 80. The same case happened at SDN Experimental Medan City. While the results in the field reported that teachers who actively teach well and liked the students experienced values below the expected standards. Therefore, "LOPEG(Teacher Pedagogical Observation Sheet):Development of instruments to analyze the feasibility of UKG results in SDN Percobaan Medan City is present as a solution, an instrument development to measure teachers' needs and accommodate the aspirations of teachers for the implementation of the UKG which is considered burdensome for teachers as workers professional educators